CONCEPT OF DISTRIBUTED FACTS POWER FLOW CONTROL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In transmission grid, for voltage and power flow control FACTS devices are used. But high cost and reliability concerns have limited the wide spread deployment of FACTS solutions. Implemented version of FACTS device, D-FACTS is introduced as a way to remove these barriers. D-FACTS device, name is distributed static series compensator DSSC, connects directly to power line. By changing line reactance of transmission line D-FACTS devices are distributed in such way that desired power flow control can be achieved effectively. Details of implementation and system impact are presented in the paper along with case study of DSSC device.